(untitled) (International Journal of Environmental Sciences, 2025)
This study offers a thorough assessment of humanitarian supply chain management (HSCM) through a systematic literature review (SLR), bibliometric analysis, and latent Dirichlet allocation (LDA) topic modelling. This research looks at 228 peer-reviewed papers from 2006 to 2025, showing the main topics, identifying important areas that need more study, and exploring how theory and practice come together in humanitarian logistics. Five main issues were identified from the analysis: methods for analyzing logistics, managing crises and building trust in supply chains, techniques for managing relief efforts, strategic approaches to humanitarian planning, and the effects of sustainability and local challenges. The report highlights the increasing significance of digital technologies like blockchain, AI, and IoT while also acknowledging their restricted practical implementation due to infrastructural and contextual limitations. It underscores the necessity for enhanced theoretical integration, especially with social and environmental sustainability, and promotes a consolidated research agenda that harmonizes innovation, inclusion, and resilience in humanitarian operations.